Cloning and expressing PfMyb2, a Plasmodium falciparum DNA-binding protein - Baker, Gillian Lee (My University, 2009)
The malaria parasite, Plasmodium falciparum, is responsible for more than 3000 deaths in Africa per day. The complex lifecycle of the parasite in the human and mosquito hosts requires a tight control of gene regulation. This area of the parasite’s biology is not well understood but recent advances in the application of molecular techniques to P. falciparum and the publication of the parasite genome sequence have provided the means to gain insight into mechanisms of gene regulation in the parasite. PfMyb2 is annotated as a putative transcription factor. It contains two Myb-like DNA-binding domains which have been cloned and demonstrated to bind Myb regulatory elements in the promoters of two P. falciparum genes, therefore validating it as a DNA-binding protein (Meyersfeld, 2005). In this study the full length PfMyb2 gene was cloned into the pGEX-4T-2 expression vector and induced to express recombinant PfMyb2 protein fused to a glutathione-Stransferase (GST) tag in E. coli. This prokaryotic expression system produced mainly insoluble recombinant protein. The protein was extracted from the bacterial inclusion bodies, solubilised, refolded and purified using affinity chromatography.A 500ml culture yielded ~20-40ug purified PfMyb2-GST in total. Bioinformatic analysis revealed homologues of PfMyb2 in other Plasmodium species and an unusually high homology to the human CDC5 protein, a multifunctional protein involved in transcriptional regulation of the cell cycle as well as in pre-mRNA splicing. PfMyb2 and CDC5 both contain a REB1 domain, part of a yeast protein. This domain binds to DNA to enhance transcription factor binding and it may also remodel chromatin resulting in activation or silencing of promoters. Based on the high homology to CDC5, including the REB1 domain, it is speculated that PfMyb2 is a multifunctional protein that plays a role in transcription, chromatin remodelling and RNA processing in the parasite. The full length recombinant PfMyb2 produced in this study lays the foundation for future studies to validate these speculative functions.